Heavy Metal Contamination in Beef Cattle on Local Community’s Health (Study Case: PT. Vale Indonesia, Sorowako Indonesia) - Jasmin Ambas; Fatmawaty Annisa Syamsuddin; Syamsuddin Hasan (PT. Anagata Sembagi Education, 2025)
Beef Cattle farming activity in post-mining site of PT. Vale Indonesia has been contaminated by heavy metals. This was indicated by 60% and 40% of produced beef from cattle farming in post-mining sites supplied to the traditional market. The study is a descriptive quantitative study employing descriptive statistics analysis. This study employed a purposive sampling method on 30 respondents consisting of 10 pregnant women, 10 teenagers (age of 10-17), and 10 adults (age of +17). The results of the study confirmed that there is the presence of potential health risks based on Sytmthoms (1) anemia, (2) headache, (3) fatigue and (4) sore throat in pregnant women for 41,43%; teenagers (age of 10-17) for 21,43% and the adults for 37,14% respectively. Although the authors found the potential health risk from the respondent, we could generalize all the symptoms come from the heavy metal contamination on beef consumed. Therefore, we need to conduct further study about the beef consumption of local communities around the post-mining area PT Vale, Indonesia.